Damage spreading in a driven lattice gas model - Rubio Puzzo, Maria Leticia (2013)
We studied damage spreading in a Driven Lattice Gas (DLG) model as a function of the temperature T , the magnitude of the external driving field E, and the lattice size. The DLG model undergoes an order-disorder second-order phase transition at the critical temperature Tc (E), such that the ordered phase is characterized by high-density strips running along the direction of the applied field; while in the disordered phase one has a lattice-gas-like behavior. It is found that the damage always spreads for all the investigated temperatures and reaches a saturation value Dsat that depends only on T . Dsat increases for T < Tc (E = ∞), decreases for T > Tc (E = ∞) and is free of finite-size effects. This behavior can be explained as due to the existence of interfaces between the high-density strips and the lattice-gas-like phase whose roughness depends on T . Also, we investigated damage spreading for a range of finite fields as a function of T , finding a behavior similar to that of the case with E = ∞.